Perceived Impact of Outsourcing within Small Medium Industry in Malaysia - Harminder Singh, Amritpall Singh (2006)
Outsourcing have long have its impression of giving positive value to firms partaking it, but recent studies have shown that it’s not necessary working for all the firms. The purpose of this paper is to show the effects of outsourcing in SME and the influence on business productivity. The framework for this study is based on Elmuti (2003) framework of perceived impact of outsourcing. A mail survey way used to a sample size of 1000 SME to answer the following objectives 1) To understand factors firms see in successful outsourcing 2) To understand why firms participate in outsourcing and what are achieved by outsourcing, 3) Evaluating effects of outsourcing on customer service management (CSM) The finding does show that the 3 main factors in successful outsourcing have to do with internal structure. Some of the firms that participate in outsourcing are achieving the desired outcome while some are having the total opposite. CSM was divided into 2 factors, one is having a negative impact from outsourcing while the other factor is having a positive impact. The findings in this paper do have some limitions, to name a few the response rate was poor, with only 71 samples used for analysis.